(3eMOOGJ GdJZjQ ai GdEfLGH ai eUQ (B2000- 2014/ s - (3YHOGdMejO eMeO Ydi GdTHQGhis; (3YHOGdZfi eMeO YHOGdZfi (B: s; (3eMeO fLjH YHOGdaJGM (B: s ((3GdbGgQI (B: s (3YHOGdMejO eMeO Ydi GdTHQGhi (B: s, 2019)
(3JgOa gPg GdOQGSI Edi aMU GdYhGed GdeHGTQI h GdhSjWI GdeDKQI ai JZjQ eYOd GdEfLGH Gdcdi ai eUQ ai YGei (B2000 (3Edi (B2014 (3h Pdc dJaSjQ GdEQJaGY GdeaGLjA ai eYOd GdEfLGH Gdcdi ai GdeSM GdScGfi GdUMi GdCNjQ (B(2014) (3h GdPi bO hUd Edi (B3,5 (3ehdhO ddSjOI HYO Cf cGfJ hUdJ bjeJg ai (B2008 (3Edi (B3 (3ehdhO ddSjOI h bO Je Yed ebGQfI Hjf GdYhGed GdeHGTQI h GdhSjWI ai YGei (B2000 (3h (B2014 (3HESJNOGe fehPL GdeYGOdGJ GdgjcdjI HGdEYJeGO Ydi eJZjQ YOO GdehGdjO ddSjOI ai GdKdGK SfhGJ GdSGHbI ddeSM (B((3GdeJZjQ GdJGHY(B) (3ceDTQ JbQjHi deYOd GdEfLGH Gdcdj (B- (3HYO GdJMbb ef JTGHg EJLGg h bhI JCKjQ GdJZjQ Hjf GdeJZjQjf (B- (3h bO CTGQJ GdfJGFL Cfg h HTcd YGe cGf gfGc JCKjQGk ddYhGed GdhSjWI Ydi YOO GdehGdjO ai GdKdGK SfhGJ GdSGHbI ddeSM Cbhi ef JCKjQ GdYhGed GdeHGTQI aj cdG GdeSMjf(B. (3cGf CYdi GdeJZjQGJ GdNGQLjI JCKjQGk Ydi NaV GdEfLGH gh GdJYQV dQSGFd JfXje GdCSQI h GdMGdI GdYedjI ddSjOI heDTQ GdKQhI h YeQ GdSjOI bHd GdKdGK SfhGJ GdSGHbI ddeSM ai YGe (B2000 : (3h bO EfNaV JCKjQ GdeJZjQGJ GdSGHbI Ydi NaV YOO GdehGdjO ai GdKdGK SfhGJ GdSGHbI ddeSM ai YGe (B2014 (3h gPG GdEfNaGV ai GdJCKjQ bO TGQc ai hUhd eYOd GdEfLGH Gdcdi ai YGe (B2014 (3Edi faS bjeJg ai YGe (B2000 (3h gi (B3,5 (3ehdhO ddSjOI(B: (3h eY GdEfJbGd Edi CKQ GdeJZjQGJ GdhSjWI afLO Cf CYdi GdeJZjQGJ GdhSjWI JCKjQGk Ydi GdEfLGH cGf GdMGLI ZjQ GdedHGI dhSGFd JfXje GdCSQI h GdJhba Yf ESJNOGe hSGFd JfXje GdCSQI ai GdNeS SfhGJ GdSGHbI h YOO eQGJ GdJhba Yf ESJNOGe hSGFd JfXje GdCSQI ai GdKdGK SfhGJ GdSGHbI ddeSM h hajGJ GdCWaGd Ohf GdNGeSI ai YGei (B2000 (3h (B2014(3ZjQ Cfg ai YGe (B2014 (3cGf GdJCKjQ GdCYdi ddJhba Yf ESJNOGe hSGFd JfXje GdCSQI ai GdNeS SfhGJ GdSGHbI h GdMGLI ZjQ edHGI Ke YOO eQGJ GdJhba Yf ESJNOGe hSGFd JfXje GdCSQI Ke h ajGJ GdCWaGd Ohf GdNGeSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddHMhK GdEMUGFjI (B- (3bSe GdEMUGA GdMjhi h GdScGfis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeJZjQGJ GdeHGTQIs; (3YOO GdehGdjO ddSjOI ai GdKdGK SfhGJ GdSGHbI ddeSMs; (3eYOd GdEfLGH Gdcdis